Development of Electronic Student Worksheets Based on Research of Potential Annona muricata L. as Antibacterial in Biology Learning - Kurnia Widiyani; Dewi Jumiarni; Bhakti Karyadi; Yennita Yennita; Sri Irawati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2021)
This study aims to produce E-LKPD teaching materials for class X bacteria based on the Inhibitory Test of Soursop Leaf Extract (Annona muricata L) against Escherichia coli bacteria, determine the feasibility of E-LKPD and determine the student response test on bacterial material. This type of research is research and development using the Borg and Gall model (1989) with stages of potential and problems, data collection, product design, design validation, and design revision. The research was conducted at the University of Bengkulu and the feasibility test was carried out by validators of media experts, material experts, and practitioner experts and continued with a response test conducted by 12 students at SMAN 8 Bengkulu City, MIPA class. The teaching materials that have been compiled and developed get a validation value from material experts 90,62% with very feasible criteria, media experts 96,42% with very feasible criteria, and 100% practitioner experts with very feasible criteria and a response test of 91,51 % with very good criteria. E-LKPD can be used to test the use of biology teaching materials for class X SMA for bacteria.